Identifikasi Tahap Pemberdayaan Masyarakat Lokal di Desa Wisata Undisan - Dewi, Ni Luh Putu Evi Sari; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i01.p19, 2023)
To develop a village into a well develop tourism village need a good quality of human resources. Empowerment is one of the best solutions to make local people join in the process of tourism activities. As a tourism village, Undisan need to have support from local people to make the village flourist. To give the best service and to make Undisan to next level people need to be educated about tourism. The purpose of this research’s to identified empower local communities in Undisan Tourism Village. Primary data sources and secondary data sources were used this study. To collect the data for this research were using three techniques. Purposive sampling technique is used to choose the informants. To analyse the data using qualitative analysis data. To help in analyzing data in this research using concept empowerment, local communities, rural tourism. The conclusion from this research is Undisan village already have good empowerment for local people. Eventhought already raach the third stage, all stage was not fully operational. Keywords: Empowerment, Local People and Rural Tourism